Penerapan Gaya Mengajar Humoris dalam Pembelajaran PAI di SMK PGRI 1 Ponorogo - Arifin Wahyudin Fatkhurahman Syah; Annisa Nur Fitriani; Arina Amalia Husna; Arina Diyas Sa'adah; Annisa Dwi Kurniawati (https://ejournal.insuriponorogo.ac.id/, 2025)
An educator should be able to manage a fun learning process, and use interactive strategies in delivering material so that students are easy to understand and feel comfortable during learning. Fun learning is proven to have a big effect on student learning outcomes. However, learning Islamic religious education sometimes only applies the lecture method and lacks differentiation, learning becomes less interesting and optimal for students. The purpose of this study is to find out the application of a humorous teaching style that can be an innovation in learning Islamic religious education which usually tends to be boring and monotonous. In this research, the method used is descriptive qualitative. Through a qualitative approach, descriptive information is obtained in the form of text sourced from several individuals and behaviors that can be observed. Data collection techniques in this research are through observation, documentation, and interviews. This research will explain the meaning of humorous teaching style, types of humor in learning, the benefits of applying humorous teaching style, and humorous teaching style applied in learning Islamic religious education at SMK PGRI 1 Ponorogo. The results showed that humorous teaching style is very important to be applied in learning. Learners who follow learning with fun will not feel bored or saturated in the classroom, will not experience frustration in learning, and will be able to remember the subject matter better.